Space syntax analysis of tourists’ movement patterns in the historical district of Kuala Lumpur, Malaysia - Mansouri, Mahsa; Ujang, Norsidah (Taylor and Francis, 2017)
Although many researchers study the walkable environment and physical activities, very few studies demonstrate the important functions of walkable places on tourists’ walking experiences, particularly in Southeast Asian cities. This article evaluates pedestrian networks’ connectivity in Kuala Lumpur’s historic district to support pedestrian tourists’ movement patterns. The methods used in this study are gate observation and space syntax (integration value) analysis. The results indicate that pedestrian movement in the study areas is oriented more to land uses and elements of attractors than to connectivity of walkways. The findings suggest that pedestrian-oriented environments could contribute to the walkability of city centers through the integration of diverse place uses and street activities. The findings can be a useful reference for future urban studies and urban design of walkability to regenerate historical city centers that have lost their importance for tourists.